Model could aid emergency response planning for foot-and-mouth disease outbreaks - M Kobayashi; R Howitt; T Carpenter (California Agriculture, 2009)
Infectious animal diseases are an ever-present threat to intensive livestock production. We analyzed control technology for foot-and-mouth disease (FMD) in a livestock-intensive region of the Central Valley, using a previously developed, numerical, optimal disease-control model. We found that the alternative FMD controls we studied (early detection, herd depopulation and vaccination) can be partially substituted for one another (substitutability) without substantially changing outbreak costs. This information can be used to develop effective and efficient policies to prepare for an FMD outbreak in California.